The relationship between spiritual health, quality of life, stress, anxiety and depression in working women - Tayebeh Rakhshani; Pari Saeedi; Seyyed Mansour Kashfi; Leila Bazrafkan; Amirhossein Kamyab; Ali Khani Jeihooni (Frontiers Media S.A., 2024)
BackgroundWhile there are benefits to women entering the workforce, there are also drawbacks, such as stress, anxiety, and depression, which can lower quality of life. However, some research indicates that women's spiritual health may be a protective factor in these situations. This study is to explore the relationship between spiritual health and quality of life, stress, anxiety, and depression among a population of women working in health care centers, given the existence of such a relationship among women.MethodsIn 2022, 500 women who worked in health centers in Izeh City, Iran, participated in this cross-sectional survey. The clustered census sampling approach was used for the sample. The research participants completed a 12-item quality of life questionnaire on spiritual health, stress, anxiety, and depression as part of the data gathering process. The data were examined using independent t tests, one-way variance, and Pearson correlation after being entered into SPSS-24.ResultsOf the participants, 18% were single and 68% were married. In terms of depression, stress, and anxiety, the mean and standard deviation were 8.26 ± 5.78, 11.26 ± 4.89, and 7.91 ± 0.98, respectively. The quality of life had a mean and standard deviation of 30.82 ± 3.56. Women who were unmarried and had more work experience reported a considerably greater quality of life (p < 0.05). The findings indicated that stress and spiritual health (p = 0.001), anxiety and spiritual health (p = 0.032), and depression and spiritual health (p = 0.024) all had a significant and inverse association. Furthermore, a strong and positive correlation was found (p = 0.001) between spiritual health and quality of life.ConclusionThe study's conclusions demonstrated a clear link between spiritual health and life satisfaction, suggesting that working women's quality of life may be raised by treatments that support spiritual health. Furthermore, the findings demonstrated a significant inverse relationship between spiritual health and the psychological variables of stress, anxiety, and depression. This suggests that by understanding the factors influencing mental health and the role of spiritual health moderator, it may be possible to improve the psychological state of employed women.